2011
DOI: 10.7705/biomedica.v30i4.292
|View full text |Cite
|
Sign up to set email alerts
|

Eficacia de la movilización y la participación social para la apropiación o “empoderamiento” (sic.) (empowerment) de las medidas de control del dengue, Comuna Norte, Bucaramanga, 2008-2009

Abstract: Movilización social y control del dengue ARTÍCULO ORIGINAL Eficacia de la movilización y la participación social para la apropiación o "empoderamiento" (sic.) (empowerment) de las medidas de control del dengue,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
0
11
0
4
Order By: Relevance
“…Outcomes used were knowledge of symptoms and transmission modalities [26, 27, 31, 55, 56], knowledge and beliefs about control measures [52], changes in people’s behaviour to control Aedes aegypti breeding sites [23–25], people’s abilities and adequate practices for controlling the vector [31], empowerment of prevention and control measures [26, 50, 52], household participation in dengue control activities [53], intersectoral participation in dengue control activities [53], and health worker capacity indicators [63]. All results from these studies were favourable to the evaluated intervention with a pre-post comparison with variable magnitudes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes used were knowledge of symptoms and transmission modalities [26, 27, 31, 55, 56], knowledge and beliefs about control measures [52], changes in people’s behaviour to control Aedes aegypti breeding sites [23–25], people’s abilities and adequate practices for controlling the vector [31], empowerment of prevention and control measures [26, 50, 52], household participation in dengue control activities [53], intersectoral participation in dengue control activities [53], and health worker capacity indicators [63]. All results from these studies were favourable to the evaluated intervention with a pre-post comparison with variable magnitudes.…”
Section: Resultsmentioning
confidence: 99%
“…The community-based trial conducted by Cáceres-Manrique et al [26] showed the efficacy of social mobilization to improve knowledge and practices and highlighted its role in public empowerment with regard to preventive and control measures—key elements to ensure the sustainability of community-based strategies. Similarly, the study by Toledo et al [44] evaluated the sustainability of an intervention strategy to achieve active participatory control over a two-year period.…”
Section: Resultsmentioning
confidence: 99%
“…La relevancia de su uso como factor protector ha sido reconocido en la literatura científica (38) y en otras experiencias en Colombia informaron sobre el incremento de su uso a partir del desarrollo de estrategias participativas (12). En este estudio no fue posible establecer cuál fue la motivación de la comunidad para el desarrollo de esta práctica.…”
Section: Discussionunclassified
“…Este hallazgo sugiere que la promoción de anjeos o cortinas impregnadas con insecticidas, podría ser una estrategia de control del dengue por evaluar en futuros estudios en Buga. (12,32,40).…”
Section: Discussionunclassified
See 1 more Smart Citation